Frontoethmoid mucocele: a case report - Mubaraki, Musleh; Albarki, Ali; Shamakhi, Radeif (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Mucoceles are cystic lesions of the paranasal sinuses that develop as a result of mucous secretion accumulation due to sinus ostium obstruction, Mucoceles are most common in the frontal and ethmoidal sinuses, and they affect both men and women equally in may become infected and spread to the orbital cavity, compressing the orbit by eroding the orbital cavity’s bony walls. In surgical treatment, endoscopic approach we are used, we present a case of a complicated ethmoid mucocele that eroded the orbital wall and spread into the orbital cavity, and we discuss surgical treatment options in light of the existing literature.